Individual Consequences of Internal Marketing - Naghi, Remus Ionut; Preda, Gheorghe (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Since the emergence of the concept of internal marketing in the literature there have been almost 40 years. This period was marked by a constant increase of the concerns in the internal marketing area, these efforts being evidenced by the publication of a consistent number of articles (conceptual and empirical) which analyze this subject. Considering the previous empirical studies, most of them have focused on studying the relationship between internal marketing and employee satisfaction and / or organizational commitment. However, the relationship between internal marketing and its consequences has been less analyzed in the context of emergent economies. In this paper we aimed to analyze the individual consequences of the internal marketing in the Romanian economy context, focusing our attention on three constructs: employee satisfaction, organizational commitment and organizational citizenship behavior. The research was conducted on a sample of 83 medium and large companies in various sectors of the Romanian economy. In order to proceed with the statistical data analyses we followed these steps: verifying the scales reliability, determining factor loadings and research hypotheses testing. Our research results are consistent with results of previous studies showing that the adoption of internal marketing practice has a positive effect on employee satisfaction, organizational commitment and organizational citizenship behavior.